Digital Storytelling as an Alternative Teaching Technique to Develop Vocabulary Knowledge of EFL Learners - Desty Laura Br Sembiring; Debora Chaterin Simajuntak (Journal of Languages and Language Teaching, 2023)
Developing vocabulary is crucial because it allows a student to be proficient in four areas (listening, speaking, reading, and writing). Students will not significantly improve their English language abilities if they lack the necessary vocabulary. The purpose of this study is to determine whether digital storytelling (DST) can replace traditional classroom instruction as a means of enhancing vocabulary knowledge. The study was carried out by utilizing a comparative research design. The participants aged from 13 to 14 years old and took grades 7 A and B of SMP N 3 Parongpong Junior High School. Pre-test, treatments, and post-tests were used to gather study data. From the results of the pre-test, it can be seen the participants' initial abilities were in a bad category with a score of less than 69. According to the initial results, this study aimed to show that the research had a significant impact on students' post-test performance as compared to their pre-test performance. The study's findings indicated that using digital storytelling helps learners in the experimental class grow their vocabulary knowledge and establish it. Throughout the treatment, learners who were taught using DST outperformed those who were not taught using DST. Furthermore, it was observed that the group with DST had a positive opinion on the utilization of digital storytelling in the classroom. The results also show how well digital storytelling involves students in the learning process.